Multiplication of contaminant bacteria in urine and interpretation of delayed culture. Issue 7 (July 1977) - Wheldon, D B; Slack, M
Abstract : A prospective study of the bacterial populations of non-infected urine was mounted in an attempt to define the length of delay between voiding and analysis during which culture would not give false positive results due to the multiplication of contaminant bacteria present at the time of voiding. The findings suggest that culture of urine within four hours of voiding is likely to give a true indication of the presence or absence of infection. With further delay the interpretation of a heavy growth of bacteria in urine becomes progressively more unreliable, even if that growth is in pure culture.